Association of Myasthenia Gravis With Autoimmune Thyroid Disease: A Bidirectional Mendelian Randomization Study - Yao Wang; Ke Wang; Jing Lu; Peng Xu; Dongmei Zhang; Xinzhi Chen; Jian Wang (Brain and Behavior)
ABSTRACT Background and Purpose Observational studies have indicated a high occurrence of coexistence between myasthenia gravis (MG) and autoimmune thyroid disease (AITD) in clinical settings, but the causal relationship between the two conditions remains ambiguous. Therefore, this study endeavors to investigate the causal links between MG, along with its subgroups, and AITD through a Mendelian randomization (MR) approach. Methods Genetic instrumental variables associated with MG and AITD were selected from three major publicly available GWAS databases for MR analysis. The primary method for evaluating causal effects was the inverse variance weighted (IVW) method. Supplementary methods included MR‐Egger regression and weighted median. The reliability and stability of the results were ensured through tests for heterogeneity, assessment of pleiotropy, and sensitivity analysis using the leave‐one‐out approach. Results The investigation revealed reciprocal causal associations between MG and both Graves’ disease and autoimmune hypothyroidism. Genetic predisposition to MG was linked to an increased likelihood of developing Hashimoto's thyroiditis (OR = 1.242(1.073–1.437, P = 0.0036)), and early‐onset MG also exhibited an association with an elevated risk of HT (OR = 1.157(1.073‐1.246), P = 1.269×10−4). No statistically significant relationships were found for the other conditions. Conclusion This extensive MR analysis provides evidence suggesting a potential association between MG and AITD, particularly with Graves' disease and Hashimoto's thyroiditis. Consequently, proactive treatment strategies targeting either MG or autoimmune thyroid disorders may help mitigate the risk of comorbidities in affected patients.